Dietary knowledge and practices among patients with diabetes in North Lebanon: the role of dietary counselling - Rosy Mitri; Zeina El-Ali (Journal of Nutritional Science)
The aim of the study is to assess the dietary knowledge and practices of Lebanese patients with diabetes not receiving dietary counselling in a low-income setting. A cross-sectional study was conducted among 317 Lebanese adult patients, not receiving dietary counselling in North Lebanon. Patients completed a questionnaire evaluating their sociodemographic, health and clinical characteristics as well as their dietary knowledge (DK) and practices. The mean total DK score as well as the mean scores for each category were calculated for the whole sample, transformed into percentages of maximal score and classified into poor (< 50%), good (50–75%) and adequate (> 75%). Patients had a good, but not optimal total DK (51.66%). Similarly, they also had a good knowledge related to carbohydrates (52.16%) and fat (52.5%), and to food type (60.83%). On the other hand, they had a poor knowledge about food choices (35.66%) and protein (44%). Linear regression analysis revealed that a higher educational level (β = 1.96, p < 0.001), choosing whole grains (β = 1.19, p = 0.002), living with a partner (β = 1.01, p = 0.007), being recently diagnosed with diabetes (β = –1.23, p = 0.012) were positively associated with a better DK. Furthermore, patients who suffered from type I diabetes had a better DK compared to those suffering from type 2 diabetes (β = –1.31, p = 0.016). The nutritional knowledge of the patients with diabetes not receiving dietary counselling is good but not optimal. Dietitians and doctors should collaborate to provide patient-centred and individualised dietary education to patients with diabetes.